Association between kaolin-induced maximum amplitude and slow-flow/no-reflow in ST elevation myocardial infarction patients treated with primary percutaneous coronary intervention. (15th December 2022) - Li, Qing; Xie, Enmin; Tu, Yimin; Wu, Yaxin; Guo, Ziyu; Li, Peizhao; Li, Yike; Yu, Xiaozhai; Ye, Zixiang; Yu, Changan; Gao, Yanxiang; Jingang, Zheng
Abstract: Background: ST-segment elevation myocardial infarction (STEMI) patients with a high thrombus burden have a relatively high slow-flow/no-reflow risk. However, the association between kaolin-induced maximum amplitude (MAthrombin ) and slow-flow/no-reflow has been scarcely explored. Methods: STEMI patients treated with primary percutaneous coronary intervention (PCI) were retrospectively enrolled from January 2015 to December 2019 at China-Japan Friendship Hospital. MAthrombin levels were measured using thromboelastography before the PCI procedure. The patients were divided into two groups according to thrombolysis in myocardial infarction (TIMI) flow grade after primary PCI: the normal flow group (TIMI flow grade = 3) and slow-flow/no-reflow (TIMI flow grade ≤ 2). The logistic regression model and restricted cubic spline regression (RCS) were used to analyze the predictive value of MAthrombin for slow-flow/no-reflow. All patients were followed up after discharge and observed the adverse cardiovascular events between the two groups. Results: A total of 690 patients were enrolled, with 108(15.7%) having slow-flow/no-reflow. The multivariate logistic regression model analysis showed that MAthrombin level was an independent risk factor for slow-flow/no-reflow. The RCS analysis showed a nonlinear relationship between MAthrombin levels and slow-flow/no-reflow. The cut-off value of MAthrombin levels for predicting slow-flow/no-reflow was 68 mm. During a median follow-up time of 4.4 years, slow-flow/no-reflow (hazard ratio 1.93, 95% confidence interval 1.27–2.93, P = 0.002) and MAthrombin levels (hazard ratio 1.06, 95% confidence interval 1.03–1.08, P < 0.001) were independent risk factors for predicting the long-term of adverse clinical cardiovascular events. Conclusion: MAthrombin was an independent risk factor for predicting slow-flow/ no-reflow in STEMI patients who underwent primary PCI. Highlights: Kaolin-induced maximum amplitude was associated with the risk of slow flow/no-reflow in ST-segment elevation myocardial patients who were treated with percutaneous coronary intervention. Kaolin-induced maximum amplitude and slow flow/no-reflow both predicted the long-term cardiovascular events risk. A high kaolin-induced maximum amplitude level was associated with a significantly increased risk of ischemia events only in ST-segment elevation myocardial patients with slow-flow/no-reflow.